From disaster to disease: Dengue outbreaks after mining dam failures in Mariana and Brumadinho, Brazil - Bianca Alves Almeida Machado; Adivane Terezinha Costa; Paulo de Tarso Amorim Castro; André Talvani (One Health)
The mining dam failures in Mariana (2015) and Brumadinho (2019), Minas Gerais, Brazil, caused catastrophic loss of life and severe environmental damage. The drastic environmental changes caused by mudflows may have contributed to an increase in vector-borne infectious diseases and other public health concerns. This study analyzed infectious disease incidence between 2014 and 2020 using data from the Brazilian DATASUS platform and on-site assessments of rivers and environmental conditions. In Mariana, schistosomiasis notifications remained minimal, while dengue infections rose by over 100 % in both Mariana and Brumadinho. Incidents involving venomous animals remained high but unrelated to mining incidents. Mining collapses appear to have contributed to the rise in dengue and schistosomiasis cases in affected areas. Integrating sustainable development goals into mining practices is crucial to preventing future incidents and the emergence of vector-borne diseases in areas affected by mining activities.